2020
DOI: 10.1021/acs.jctc.0c00977
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Coupled-Cluster Many-Electron Dynamics in Terms of Stationary States

Abstract: We demonstrate theoretically and numerically that laser-driven many-electron dynamics, as described by bivariational time-dependent coupled-cluster (CC) theory, may be analyzed in terms of stationary-state populations. Projectors heuristically defined from linear response theory and equation-of-motion CC theory are proposed for the calculation of stationary-state populations during interaction with laser pulses or other external forces, and conservation laws of the populations are discussed. Numerical tests of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 90 publications
(205 reference statements)
0
25
0
Order By: Relevance
“…It has been shown that making the above action (Equation 10) stationary with respect to time-dependent orbitals leads to dynamics that satisfy Ehrenfest's theorem for all 1-electron operators 2,17,18,53,55 . This can be important because, as pointed out by Pedersen et al 55 , it leads to local conservation and gauge invariance in 1-electron properties.…”
Section: B Coupled Cluster Dynamics With Time-dependent Orbitalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that making the above action (Equation 10) stationary with respect to time-dependent orbitals leads to dynamics that satisfy Ehrenfest's theorem for all 1-electron operators 2,17,18,53,55 . This can be important because, as pointed out by Pedersen et al 55 , it leads to local conservation and gauge invariance in 1-electron properties.…”
Section: B Coupled Cluster Dynamics With Time-dependent Orbitalsmentioning
confidence: 99%
“…In ab initio electron dynamics, a variety of methods have been applied to simulate various phenomena, such as multiple photon processes 1 , high harmonic generation 2 , and ultrafast laser dynamics 3 in atomic and molecular systems. Among them are time-dependent density functional theory 4 and wavefunction based methods such as time-dependent Hartree-Fock 5 , configuration interaction (CI) [6][7][8][9] , complete-active-space self-consistent field (CASSCF) 2 , multiconfigurational time-dependent Hartree-Fock [10][11][12] , density matrix embedding theory (DMET) 13 and coupled cluster (CC) methods [14][15][16][17][18] . Ab initio electron dynamics in materials has primarily been carried out at the time-dependent density functional theory level, although studies with low-order diagrammatic approximations have begun to appear 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time coupled cluster (RT-CC) methods, in particular, can achieve exceptionally high accuracy in many cases 17,18 and have been explored in the context of real-time simulations for some years. [9][10][11][19][20][21][22][23][24][25][26][27] However, RT-CC approaches also suffer from the same affliction as that of their time-independent counterparts, viz., high-degree polynomial scaling with the size of the molecular system. For ground-state coupled cluster theory, techniques such as local correlation, [28][29][30][31][32][33][34][35] fragmentation, [36][37][38][39] tensor decomposition, [40][41][42][43][44][45] and others have been developed to permit applications to larger molecular systems than conventional implementations allow.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these early endeavours, real-time methods did not become practical at that time due to the lack of electron correlation effects at the Hartree-Fock level and the high computational cost associated with propagation of correlated wave functions. However, decades of steady advancements in computing power and numerical algorithms have led to a renewed interest in explicit time propagation in correlated methods like density functional theory [12,13], multiconfigurational selfconsistent-field [14][15][16], configuration interaction [17][18][19][20], algebraic diagrammatic construction [21,22] and coupledcluster [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%